Quantitative Ansätze in den Literatur- und Geisteswissenschaften Systematische und historische Perspektiven - Bernhart, Toni; Willand, Marcus; Richter, Sandra (De Gruyter, 2018)
Since the beginning of the 19th century, quantitative techniques have been used in literary and human sciences to describe, analyze and interpret texts. Such approaches were underrepresented until the end of the 20th century, but are becoming increasingly important in the digital humanities. The aim of the volume is to contextualize theories of theory, methodology and subject history on the one hand, and on the other hand to examine the significance of their results with a view to the digital present. In view of the innovative verve of digital humanities, it should not be forgotten that the idea of ​​juxtaposing interpretive close reading with descriptive-analytical, remote reading is not much younger than the idea of ​​close reading itself. Counting is by no means the first through the 'digital revolution' of the humanities. Rather, what has been determined by late Dilthey as the subject of the understanding and qualitatively oriented humanities has been declared 'measurable' for some 200 years.